Strophanthus sarmentosus Extracts and the Strophanthus Cardenolide Ouabain Inhibit Snake Venom Proteases from Echis ocellatus - Julius Abiola; Olapeju Aiyelaagbe; Akindele Adeyi; Babafemi Ajisebiola; Simone König (Molecules)
Strophanthus sarmentosus is recognised for various ethnomedicinal applications, including treatment after snakebites. However, only limited scientific evidence exists on its antivenomous capabilities. This study investigates the efficacy of methanol and ethylacetate extracts from S. sarmentosus leaves and roots against Echis ocellatus venom. A non-toxic range for the extracts was determined in rats, and assays were performed to test their anti-hemorrhagic and anti-hemolytic activity as well as their influence on venom-induced blood clotting. In all of these experiments, the extracts demonstrated significant positive effects equal to or better than antivenom. Moreover, the extracts strongly inhibited and even abolished the digestion of the vasoactive neuropeptide bradykinin by snake venom metalloproteinases. Strophantus plants are known for their high content of cardiac glycosides, one of which is the commercially available ouabain, that by itself also considerably inhibited venom-induced bradykinin cleavage. Although ouabain is only present in low amounts in S. sarmentosus when compared to other cardenolides of similar structure, it can be hypothesized that members of this substance class may also have inhibitory properties against venom proteases. S. sarmentosus additionally contains bioactive substances such as flavonoids, terpenoids, tannins, saponins, and alkaloids, which contribute to its protective effects. The study provides scientific data to explain the success of the traditional use of S. sarmentosus plant extracts as a first aid against envenomation in rural Africa.